The Effect of an Education Intervention on Mental Health Literacy among Middle School Female Students - Hadi Tehrani; Samira Olyani (Mashhad University of Medical Sciences, 2021)
Background and Objective: Enhancing the mental health literacy(MHL) through school-based education intervention may encourage mental health promotion, prevention, and care and reduce stigma in adolescents. The present study aimed to determine the eﬀect of educational intervention on MHL among middle school female students in Mashhad.   Materials and Methods: A quasi-experimental study was carried out on 140 female students aged between 13-15 years from two governmental middle schools in 2019 Mashhad, Iran. A multistage sampling method was used. First, one education area was randomly selected andtwo middle schools were randomly selected from this area. One middle school was considered as intervention setting and the other middle school considered as control setting. Atotal of 70 students were randomly selected from each school and allocated into two intervention and control group. Mental Health Literacy Scale (MHLS) was used to estimate MHL among student in two stages (before and after intervention). The intervention group were received four training  sessions (90 minutes) based on MHL concept. Descriptive, Paired t-test, independent sample t-test and Chi-square test were used to analyze the data using spss21 software..   Results: Before the intervention, the two groups had no significant difference in the mean score of MHL (P>0.05). After the intervention, the mean score of MHL increased from 10.5±1.34 to 17.27±11.33 in the intervention group which was statistically significant (p <0.001).   Conclusion: Designing and implementing educational interventions can promote MHL of middle school female students.